СВЯЗЬ КРЕАТИВНОСТИ С ПСИХОЛОГИЕЙ УЧИТЕЛЯ В ПРОЦЕССЕ ОБУЧЕНИЯ ГРАМОТЕ НАЧАЛЬНЫХ КЛАССОВ - Акобирова Малика Бурановна (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the primary grade as one of the most complex areas of human labor of pedagogical activity in the formation of creative abilities of students with visual impairments. In our current society, the teacher, as a person in a progressive thinking position, should acquire his modern knowledge, be tirelessly inquisitive and selfless, because the process that cannot be delayed will save the individual from intellectual and spiritual poverty. A great responsibility is required from the teacher in this regard. The implementation of modern standards requires the teacher not only high qualifications and constant professional development, but also a creative approach to his work.